2022
DOI: 10.1007/s11101-022-09806-3
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid mediated selective cross-talk between plants and beneficial soil microbiome

Abstract: Plants generate a wide variety of organic components during their different growth phases. The majority of those compounds have been classified as primary and secondary metabolites. Secondary metabolites are essential in plants’ adaptation to new changing environments and in managing several biotic and abiotic stress. It also invests some of its photosynthesized carbon as secondary metabolites to establish a mutual relationship with soil microorganisms in that specific niche. As soil harbors both pathogenic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 129 publications
0
23
0
Order By: Relevance
“…In addition, Fe 3 O 4 NMs significantly improved genistin content by 119.4–624.7% compared to the unexposed control and EDTA-Fe treatments, Fe–P NMs increased daidzein content by 14.8% in rhizosphere soil compared to the unexposed control (Figure S8). The up-regulation of flavonoids in the rhizosphere by Fe-based NMs could facilitate cross-talk between the soybean and rhizosphere microbiome, and trigger the activation of nodulation genes to start legume-rhizobium symbiosis …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Fe 3 O 4 NMs significantly improved genistin content by 119.4–624.7% compared to the unexposed control and EDTA-Fe treatments, Fe–P NMs increased daidzein content by 14.8% in rhizosphere soil compared to the unexposed control (Figure S8). The up-regulation of flavonoids in the rhizosphere by Fe-based NMs could facilitate cross-talk between the soybean and rhizosphere microbiome, and trigger the activation of nodulation genes to start legume-rhizobium symbiosis …”
Section: Resultsmentioning
confidence: 99%
“…The up-regulation of flavonoids in the rhizosphere by Fe-based NMs could facilitate cross-talk between the soybean and rhizosphere microbiome, and trigger the activation of nodulation genes to start legume-rhizobium symbiosis. 49 Flavonoids are scarcely synthesized in organs or plants grown in the dark because the expression of chalcone synthase (CHS) genes is highly dependent on light. 50 Long-distance transport from shoot to root of flavonoids has been confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…Important features of Rhizobium along with non‐rhizobial endophytes such as Bacillus, Paenibacillus, Micromonospora, Flavobacterium, Pseudomonas, Paracoccus and Novosphingobium were highlighted in this study. These were found in all domains of horse gram with many interesting functional traits, such as nutrient acquisition (Dhole & Shelat, 2022), drought mitigation (Verma et al, 2021), secondary metabolite defence system against phytopathogens (Bag et al, 2022), and signalling mechanisms through root exudates (Chialva et al, 2022). Overall, we found that a persistent survival rate over spatial and temporal dynamic patterns existed among the diverse and abundant beneficial microbes with many functional traits present in all sequential ecological zones (soil, rhizosphere region, root nodules and seeds).…”
Section: Discussionmentioning
confidence: 99%
“…Pathway analysis results showed that the major pathways involved within 5 days of inoculation were related to the biosynthesis of secondary metabolites, phenylpropanoids and flavonoids ( Thomas et al., 2019 ; Wiggins et al., 2022 ). Bag et al. (2022) suggested that secondary metabolites are crucial for plants’ adaptation to new changing environments and biotic and abiotic stress management.…”
Section: Discussionmentioning
confidence: 99%
“…Pathway analysis results showed that the major pathways involved within 5 days of inoculation were related to the biosynthesis of secondary metabolites, phenylpropanoids and flavonoids (Thomas et al, 2019;Wiggins et al, 2022). Bag et al (2022) suggested that secondary metabolites are crucial for plants' adaptation to new changing environments and biotic and abiotic stress management. Two pathways, viz., "Plant pathogen interaction" and "MAPK signaling," were specific to RG, whereas the pathways related to nitrogen metabolism and plant hormone signaling were specific to RB.…”
Section: Differential Regulation Of Metabolic Pathways In Rice and So...mentioning
confidence: 99%